Assessing the role of master plans in city development: reform measures and approaches - Nallathiga, Ramakrishna (2015)
Master plans have emerged as the standard instruments of planning to be developed by urban local governments in India. Master plans are forward planning tools that anticipate urban development and make provisions for it on city space in terms of (a) the allocation of land for various uses, (b) the regulation of its development and (c) the provision of civic infrastructure. However, they have received an increasing amount of criticism on several grounds. First of all, plan-making process is not in-line with that suggested under UDPFI guidelines and several States are at different stages of plan development. Second, it is also held that the approach of master plan is far too simplistic, especially to anticipate development needs/citizens' aspirations; their very long tenure has been a major hindrance to anticipate socio-economic and technological changes over time. Third, most of the plans are not co-terminus with urban local government, which leads to interventions at later stage or in implementation stage by obtaining deviations from plan proposals. Fourth it is also held that master plan formats fails to meet the aspirations/expectations of citizens (due to elite capture and lip-service to public participation). Finally, the approach taken towards plan implementation is fraught with financial challenges and also the risks of legal challenges of land acquisition. Planning system in Indian States needs to be overhauled and streamlined so that some of the above challenges are met. Plans have to move beyond the traditional straight jacket approach and adopt strategic and project dimensions. Plan implementation needs to be given more serious attention especially through pro-active proposals, incentive-based policy, adoption of complimentary instruments and utilising land based instruments. It is hoped that with reforms and renewal of planning system, plan making and modified approach, the plans would become successful in meeting their objective. - Reproduced.
Keywords: Urban development; Urban planning